Tantangan dan Kesempatan dalam Pembelajaran Matematika Menggunakan Flipped Classroom - Dian Permatasari (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2022)
The existence of technology in the teaching and learning process has changed the way teachers transfer their knowledge to their students. Moreover, the COVID-19 pandemic has impelled the use of technology in learning. The existence of flipped classroom has positive influences on the effectiveness of learning in understanding the basic concepts, joyful learning, student’s achievement, and collaborative learning between students. Some challenges arise in the employment of flipped classroom in the actual classroom. Therefore, this article is intended to explore the various challenges of learning mathematics in the flipped classroom model in the pandemic era. Teachers, who generally use traditional teaching as their method, find several problems regarding the way to manage and design the flipped classroom model in their teaching practice. To learn more about the flipped classroom design, teachers should expand their knowledge through training or collaborative study with professionals or experts in the flipped classroom. This is essential because it supports teachers to organize learning well.